2022
DOI: 10.3390/biomedicines10030595
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin Alleviates Ferroptosis-Associated Renal Injury, Inflammation, and Fibrosis in a Unilateral Ureteral Obstruction Mouse Model

Abstract: Nobiletin (Nob), a critical active flavonoid of citrus fruits, has received attention for its superior physical functions, which have shown to improve the progression of diseases. Chronic kidney disease (CKD) is recognized as a global health problem, and its mortality and morbidity rates are worsened with an increased risk of accompanying disorders. In this study, we aimed to elucidate whether Nob treatment ameliorates kidney fibrosis and also to identify the potential signaling networks in a unilateral ureter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…Inconsistency in these results might be attributed to the fact that the antibody cocktail (OXPHOS) employed to identify CII protein levels detects the succinate dehydrogenase (SDH) B subunit, the most labile protein used for this antibody. This protein contains three iron-sulfur (Fe-S) clusters, making the SDH8 protein more sensitive to oxidative damage, which is found in UUO [ 14 , 61 ]. Moreover, the CII is composed of three additional subunits that enhance its activity: SDHA, SDHC, and SDHD, which do not have Fe-S clusters [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistency in these results might be attributed to the fact that the antibody cocktail (OXPHOS) employed to identify CII protein levels detects the succinate dehydrogenase (SDH) B subunit, the most labile protein used for this antibody. This protein contains three iron-sulfur (Fe-S) clusters, making the SDH8 protein more sensitive to oxidative damage, which is found in UUO [ 14 , 61 ]. Moreover, the CII is composed of three additional subunits that enhance its activity: SDHA, SDHC, and SDHD, which do not have Fe-S clusters [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol nanoparticles can repress erastin-induced ferroptosis in HT22 mouse hippocampal cells [226], and also inhibits acrolein-induced ferroptosis and insulin secretion disorder via the ER-stress-related PERK pathway in mouse pancreatic β cells [227]. Nobiletin, a critical active flavonoid in citrus fruits, was found to reduce ferroptosis-related renal injury, inflammation, and fibrosis in a unilateral ureteral obstruction mouse model [228]. Nobiletin triggers the ferroptosis of human skin melanoma cells via the GSK3β-mediated Keap1/Nrf2/HO-1 signaling pathway [229].…”
Section: Regulatory Effects Of Food-borne Active Ingredients On Ferro...mentioning
confidence: 99%
“…Oxidative stress occurs when the balance between ROS and reactive nitrogen species and the antioxidant defense system is disrupted, that is, when the production of pro-oxidants or ROS exceeds the endogenous antioxidant capacity (Sies et al, 2017). It has been shown that oxidative stress promotes the progression of RF (Aranda-Rivera et al, 2021); if oxidative stress is suppressed, RF can be attenuated (Liao et al, 2022;Lo et al, 2022). Antioxidant enzymes, such as superoxide dismutase (SOD), catalase, and glutathione peroxidase (GSH-Px), protect cells from damage caused by oxygen free radicals.…”
Section: Cordyceps Attenuates Oxidative Stressmentioning
confidence: 99%